Pathogens and Antibiogram of Blood Stream Isolates in Neonatal Sepsis: Findings from a Tertiary Care Hospital, Bangladesh - Akter, Shirin; Chaudhury, Israt Jahan; Jahan, Mosammad Alpana; Sah, Subhash; Mannan, Abdul (Integrative Journal of Medical Sciences, 2022)
Background: Neonatal sepsis is associated with increased mortality and morbidity, including neurodevelopmental impairment and prolonged hospital stay. The organism responsible for neonatal sepsis may vary across geographical boundaries, even from institution to institution, and with the time of illness; thus, periodic surveillance is necessary. Therefore, the present study was conducted to determine the common pathogens and their antibiotic sensitivity pattern. Objectives: This study isolates the bacterial agents causing neonatal sepsis and determines the sensitivity pattern of the causative bacterial agents. Methods: This cross-sectional study was carried out in the neonatal intensive care unit of BSMMU from December 2012 to July 2013. Neonates (0–28 days) who were admitted to the neonatal intensive care unit with suspected sepsis were included in this study. After admission, written informed consent from parents was obtained, the baby received emergency care, and then septic screening along with blood culture and antimicrobial sensitivity testing was conducted. All data were compiled, tabulated, and then analyzed using SPSS V.12 according to the study’s objectives. Results: A total of 94 newborn babies with suspected sepsis were included in this study. Most babies (54.3%) were admitted within 24 hours after birth, 86.17% were preterm, and 81.92% of babies’ birth weight was <2500 gm. There was a preponderance of male babies over females, 53% male and 47% female. Among the suspected septic newborns, 27.66% of babies had culture-positive sepsis and 73.41% had culture-negative sepsis. Among the culture-positive cases, 72% of babies developed late-onset sepsis and 28% developed early-onset sepsis. The isolates from blood culture were Klebsiella pneumoniae in 9 (34%) cases, E. coli and Acinetobacter were found in 6 (23%) cases, Staphylococcus was found in 2 (8%) cases, and Pseudomonas, Enterobacter, and Citrobacter were found in 1 (4%) case. Gram-negative organisms were more predominant than Gram-positive bacteria. The commonly isolated organisms were most sensitive to imipenem, ciprofloxacin, colistin, and netilmicin. Almost all organisms were resistant to ampicillin and gentamicin. Conclusion: Klebsiella pneumoniae is the most common organism responsible for neonatal sepsis in BSMMU. There is an overall decline in antibiotic susceptibility to commonly isolated bacterial pathogens.